2012
DOI: 10.1016/s0140-6736(12)60834-4
|View full text |Cite
|
Sign up to set email alerts
|

From personal survival to public health: community leadership by men who have sex with men in the response to HIV

Abstract: Community leadership and participation by gay men and men who have sex with men (MSM) have been central to the response to HIV since the beginning of the epidemic. Through a wide array of actions, engagement of MSM has been important in the protection of communities. The connection between personal and community health as drivers of health advocacy continue to be a powerful element. The passion and urgency brought by MSM communities have led to the targeting and expansion of HIV and AIDS research and programmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 60 publications
3
81
0
1
Order By: Relevance
“…Moreover, nearly half of participants did not know the HIV status of their most recent client, and 86.0% did not use a condom during the most recent sex with a client, considerably higher than reported in studies among MSW in other countries, including in Asian, Latin America and Europe (Ballester-Arnal, Gil-Llario, Salmeron-Sanchez, & Gimenez-Garcia, 2014). Both behaviors are demonstrated risk factors for HIV/ STI infection among MSM (S. Baral et al, 2009; Fan et al, 2012; Koblin et al, 2006; Trapence et al, 2012). In a study of 500 MSW living in Beijing, China, for example, Fan et al found that not knowing the HIV status of the most recent male partner was associated with HIV infection (Fan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, nearly half of participants did not know the HIV status of their most recent client, and 86.0% did not use a condom during the most recent sex with a client, considerably higher than reported in studies among MSW in other countries, including in Asian, Latin America and Europe (Ballester-Arnal, Gil-Llario, Salmeron-Sanchez, & Gimenez-Garcia, 2014). Both behaviors are demonstrated risk factors for HIV/ STI infection among MSM (S. Baral et al, 2009; Fan et al, 2012; Koblin et al, 2006; Trapence et al, 2012). In a study of 500 MSW living in Beijing, China, for example, Fan et al found that not knowing the HIV status of the most recent male partner was associated with HIV infection (Fan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…1,3 These health inequities have raised awareness among community groups, donors, public health practitioners, researchers, and national AIDS programmes of the urgent need to improve HIV prevention and treatment services for MSM across the continent. 46 However, alongside increased attention to the needs of MSM is a growing social and political pushback to sexual and gender minority rights in many low-income and middle-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…Bringing community members from different sectors together as part of the event created a strong sense of community ownership. Community engagement has been championed as a key component of HIV campaigns 16. In addition, our data suggest that this type of approach can generate novel and efficient solutions.…”
Section: Discussionmentioning
confidence: 74%